2016
DOI: 10.1590/s01518-8787.2016050006680
|View full text |Cite|
|
Sign up to set email alerts
|

ERICA: use of screens and consumption of meals and snacks by Brazilian adolescents

Abstract: OBJECTIVE To describe the length of exposure to screens and the prevalence of consumption of meals and snacks by Brazilian adolescents in front of screens.METHODS We evaluated 74,589 12 to 17-year old adolescents from 1,247 schools in 124 Brazilian municipalities. A self-administered questionnaire was used. Its segment regarding nutrition contained questions about using TV, computers, and video game systems, having meals while watching TV, and consuming snacks in front of screens. Consumption of meals and snac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
51
0
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 25 publications
4
51
0
15
Order By: Relevance
“…Entre os efeitos observados, o aumento da inatividade física nesta faixa etária tem preocupado pesquisadores e especialistas 1,4,5 . No Brasil, os dados disponíveis sobre adolescentes têm demostrado elevadas prevalências de inatividade física 1,10 . …”
Section: Introductionunclassified
See 1 more Smart Citation
“…Entre os efeitos observados, o aumento da inatividade física nesta faixa etária tem preocupado pesquisadores e especialistas 1,4,5 . No Brasil, os dados disponíveis sobre adolescentes têm demostrado elevadas prevalências de inatividade física 1,10 . …”
Section: Introductionunclassified
“…As regiões Sul e Nordeste estão entre as que possuem as maiores prevalências de adolescentes que não cumprem a recomendações de atividade física (56,1% e 57%, respectivamente) e 25% não realizam atividade física 1,10 . As atuais evidências permitem demonstrar informações importantes sobre o nível de atividade física e os fatores associados para a prática de atividade física 8,9 , tais como: sexo, idade, classe econômica, apoio social e a percepção de barreiras [11][12][13] .…”
unclassified
“…Isso pode estar relacionado ao nível de instrução e à rotina de trabalho dos pais, uma vez que, para a realização das refeições à mesa e para o incentivo à prática de atividade fí-sica, o apoio familiar é importante, tanto quanto a conscientização dos próprios adolescentes. As telas de computadores e televisões têm ocupado lugar de destaque no âmbito familiar, levando a profundas mudanças no estilo de vida da população 10 . Pesquisas com 215 adolescentes (15-19 anos) foram realizadas para estimar a condição de saúde bucal e verificar a existência de impacto na qualidade de vida, e verificou-se que a maioria desses adolescente mora com os pais, cursaram o ensino fundamental em uma instituição pública de ensino, possui mães que concluíram o ensino médio e suas famílias recebem entre dois e três salários mínimos de renda mensal bruta.…”
Section: Introductionunclassified
“…Tavares et al 14 , evaluating the factors associated with low adhesion to the treatment of chronic diseases, found 30.8% of low adhesion and verified that the problem is more prevalent in the Northeast and Midwest regions of the Country. The authors indicate the actions required to improve the levels of adhesion.…”
mentioning
confidence: 96%
“…Tavares et al 14 analyzed the free access to medicines for chronic diseases and reported that 47.5% of Brazilians with these diseases obtained all the medicines they needed free of charge. The percentage of free access was higher among individuals of low socioeconomic status, but with differences regarding geographic regions and classes of medicines.…”
mentioning
confidence: 99%